Effects of ibuprofen on exercise-induced muscle soreness and indices of muscle damage. Issue 3 (September 1990) - Donnelly, A E; Maughan, R J; Whiting, P H
Abstract : Thirty-two volunteers participated in a two-period crossover study in which ibuprofen was tested against an identical placebo for its effectiveness in reducing muscle soreness and damage after two bouts of downhill running. Subjective soreness, quadriceps isometric strength and isometric endurance time at 50 percent of maximum strength, serum activities of creatine kinase, lactate dehydrogenase and aspartate transaminase and serum levels of creatinine and urea were recorded at intervals up to 72 hours after exercise. Each downhill run produced muscle soreness, and a decline in muscle strength and 50 percent endurance time, although these parameters were unaffected by ibuprofen treatment. All serum parameters measured increased after both runs, but for the three enzymes this increase was smaller after the second run. Serum creatine kinase and urea levels were higher in the ibuprofen group after both runs. These results indicate that ibuprofen is not an appropriate treatment for delayed onset muscle soreness and damage.